(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The following essay focuses on the origins of Italian Constitution and on Founding Fathers’ idea of human rights. The author describes the developments since the entry into force of the Italian Constitution, emphasizing in particular the so called Constitutionalisation of legal system. This process has shifted the focus from the authority of State to the individual, contributing to the origins of Biolaw’s study. Two opposite extremes can compromise the recognition of the biorights: the trend to transform every personal desire in a right, on the one hand, and a paternalistic attitude, on the other hand.